Lessons learnt running distributed and remote mixed reality experiments - Steed, Anthony; Archer, Daniel; Brandstätter, Klara; Congdon, Ben J.; Friston, Sebastian; Ganapathi, Priya; Giunchi, Daniele; Izzouzi, Lisa; Park, Gun Woo (Warren); Swapp, David; Thiel, Felix J. (Frontiers in Computer Science, 2023)
One traditional model of research on mixed-reality systems, is the laboratory-based experiment where a number of small variants of a user experience are presented to participants under the guidance of an experimenter. This type of experiment can give reliable and generalisable results, but there are arguments for running experiments that are distributed and remote from the laboratory. These include, expanding the participant pool, reaching specific classes of user, access to a variety of equipment, and simply because laboratories might be inaccessible. However, running experiments out of the laboratory brings a different set of issues into consideration. Here, we present some lessons learnt in running eleven distributed and remote mixed-reality experiments. We describe opportunities and challenges of this type of experiment as well as some technical lessons learnt.